Effect of organic inputs on organic seed production of pot marigold (Calendula officinalis L.) - لیلا تبریزی; علیرضا کوچکی (علوم و فناوری بذر ایران)
In order to investigate the effect of organic fertilizers on yield and seed quality criteria of Calendula officinalisL., seeds of a field experiment under application of two levels of cattle manure (without and with 20 t ha-1) and four levels of bacterial inoculant (containing N-fixing bacteria, P solubilizerbacteria, mixture of bacteria and control) were evaluated for seed quality criteria in a factorial experiment based on completely randomized design with four replications in Medicinal Plant Laboratory of Department of Horticultural Sciences and Landscape, University of Tehran in 2010 and 2011. Then, 1000 seed weight, seed yield and dimension and seed germination quality criteria such as seed germination percentage, rate and uniformity, time to 95% germination, seedling weight and length and seed vigour index were investigated. Results indicated that interaction effect of manure and bacterial inoculant caused significantly the highest 1000 seed weight and seed yield in both years. Nearly, all criteria related to seed dimension affected by cow manure and also bacterial inoculants in both years. Also, application of cow manure significantly affected seed germination percentage, seedling length and seed vigour index (both years) and inoculation of seed by plant growth promotion bacteria showed significant effects on seed germination percentage, seedling length and seed vigour index (both years) and seed germination uniformity, time to 95% germination and seedling weight (first year). In general, using cattle manure and also plant growth promotion bacteria resulted in the highest amount of all measured criteria compared to non application of manure and bacterial inoculants.